Culture of fecal indicator bacteria from snail intestinal tubes as a tool for assessing the risk of Opisthorchis viverrini infection in Bithynia snail habitat - Courtney C. Nawrocki (Parasites & Vectors, 2019)
Abstract Background Like many trematodes of human health significance, the carcinogenic liver fluke, Opisthorchis viverrini, is spread via fecal contamination of snail habitat. Methods for assessing snail exposure to fecal waste can improve our ability to identify snail infection hotspots and potential sources of snail infections. We evaluated the feasibility of culturing fecal indicator bacteria from Bithynia snail intestinal tubes as a method for assessing snail exposure to fecal waste. Snails and water samples were collected from a site with a historically high prevalence of O. viverrini infected snails (“hotspot” site) and a site with historically no infected snails (“non-hotspot” site) on two sampling days. Snails were tested for O. viverrini and a stratified random sample of snails from each site was selected for intestinal tube removal and culture of gut contents for the fecal indicator bacteria, Escherichia coli. Water samples were tested for E. coli and nearby households were surveyed to assess sources of fecal contamination. Results At the hotspot site, 26 of 2833 Bithynia siamensis goniomphalos snails were infected with O. viverrini compared to 0 of 1421 snails at the non-hotspot site. A total of 186 snails were dissected and cultured. Escherichia coli were detected in the guts of 20% of uninfected snails, 4% of O. viverrini-positive snails and 8% of snails not examined for cercarial infection at the hotspot site. Only one of 75 snails from the non-hotspot site was positive for E. coli. Accounting for sampling weights, snails at the hotspot site were more likely to have gut E. coli than snails from the non-hotspot site. The concentration of fecal indicator bacteria in surface water was higher at the hotspot vs non-hotspot site on only the first sampling day. Conclusions Fecal indicator bacteria can be detected in the intestinal tubes of Bithynia snails. The presence of fecal indicator bacteria in Bithynia snail guts may indicate risk of O. viverrini infection in snail populations. This method has the potential to aid in identifying locations and time windows of peak snail infection risk and may be applicable to other trematodes of human-health significance.